TA’DIB SEBAGAI UPAYA REKONSTRUKSI PENDIDIKAN ISLAM PERSPEKTIF SYED NAQUIB AL-ATTAS - Ahmad Suyuthi (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
of Syed Muhammad Naquib al-Attas on the fundamental concepts of Islamic education is the concept of ta'dib. For him the most fundamental issues in Islamic education is the loss of civilized values in a general mean. This is more due to the confusion of understanding in the term of tarbiyah, ta’lim dan ta’dib. Al-Attas is more likely to use the term ta'dib to the concept of Islamic educationbecause if the concept of ta’dib is applied in a comprehensive, integral, and systematic practice of Islamic education, the various human resource development issues Muslims are expected to be overcome. Moreover, in Islamic history Muslim educational process is more likely to sense ta'dib than tarbiyah or ta’lim. More fundamental reason is closely related to the science of manners, because science can not be taught or transmitted to students unless the person had the proper culture to knowledge in various fields. The concept of Islamic education is only limited to the meaning tarbiyah and ta’lim have been possessed by the Western worldview based on the values of dualism, secularism, humanism, and Sufism so civilized values become increasingly blurred and increasingly distant from the values of hikmah Ilahiah. Ambiguity civilized values or civilized destruction resulted in injustice, ignorance, and insanity.